2016
DOI: 10.1063/1.4946878
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of lithium atom under weakly coupled plasma environment

Abstract: The Rayleigh-Ritz variational technique with a Hylleraas basis set is being tested for the first time to estimate the structural modifications of a lithium atom embedded in a weakly coupled plasma environment. The Debye-Huckel potential is used to mimic the weakly coupled plasma environment. The wave functions for both the helium-like lithium ion and the lithium atom are expanded in the explicitly correlated Hylleraas type basis set which fully takes care of the electron-electron correlation effect. Due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 89 publications
0
10
0
Order By: Relevance
“…We have compared our numerical results for different screening parameters ( ) with the data available in the literature. [53][54][55]57,58] For instance, the present composite variational technique produces energy eigenvalue of the "free" 1s 2 2s ( 2 S) state of Li atom as −7.47805466 a.u. In contrast, Dutta et al [55] reported the same as −7.478012 and −7.478056 a.u.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have compared our numerical results for different screening parameters ( ) with the data available in the literature. [53][54][55]57,58] For instance, the present composite variational technique produces energy eigenvalue of the "free" 1s 2 2s ( 2 S) state of Li atom as −7.47805466 a.u. In contrast, Dutta et al [55] reported the same as −7.478012 and −7.478056 a.u.…”
Section: Resultsmentioning
confidence: 99%
“…[53][54][55]57,58] For instance, the present composite variational technique produces energy eigenvalue of the "free" 1s 2 2s ( 2 S) state of Li atom as −7.47805466 a.u. In contrast, Dutta et al [55] reported the same as −7.478012 and −7.478056 a.u. with Larson's basis set [59] and with Frolov's basis set, [60] respectively, while the best available result is reported by Puchalski and Pachuki [58] as −7.4780603238897 a.u.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations